1966
DOI: 10.1002/aja.1001180308
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the lymphatic capillary and the adjoining connective tissue area

Abstract: The lymphatic capillaries possess salient morphological features which differentiate them from the blood capillaries. Instead of a definitive basement lamina surrounding the lymphatic wall, there are numerous fine filaments (about 60 A in diameter) that are attached to the lymphatic endothelia at areas of increased electron density that are similar to half desmosomes. The filaments extend for varying distances into the adjoining connective tissue area and seem to anchor the lymphatic vessel to the surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
2

Year Published

1973
1973
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(121 citation statements)
references
References 46 publications
5
114
0
2
Order By: Relevance
“…1, 2, 3, and 4, respectively. In all instances the intima consisted of an unbroken endothelium displaying ultrastructural features now recognized as characteristic oflymphatic endothelial cells (1,2,20,37,39), including an attenuated basal lamina.…”
Section: Integrity Of Perfused Lymphaticsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, 2, 3, and 4, respectively. In all instances the intima consisted of an unbroken endothelium displaying ultrastructural features now recognized as characteristic oflymphatic endothelial cells (1,2,20,37,39), including an attenuated basal lamina.…”
Section: Integrity Of Perfused Lymphaticsmentioning
confidence: 99%
“…Regardless of its relative importance in lymph formation, a question subject to much debate, intercellular transport in vivo is heavily dependent upon adluminally directed convective forces (11,20,21). The ultrastructural analyses of the present study showed no essential differences in any intercellular contact-related variable among the groups.…”
Section: Interendothelial Contactsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is also due to the contraction of surrounding skeletal muscles, as well as arterial pulsations. Like veins, the larger lymphatic vessels contain one-way intraluminal valves that aid in lymph propulsion by preventing backXow (Leak and Burke 1966;von der Weid and Zawieja 2004). Compared to blood vessels, the lymphatic vasculature is a low Xow and low pressure system.…”
Section: Introductionmentioning
confidence: 99%